ANALISIS PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SEKOLAH DASAR NEGERI 005 KELURAHAN AIR PUTIH KECAMATAN SAMARINDA ULU KOTA SAMARINDA - Angin Ding, Agnes (PREDIKSI, 2016)
ABSTRACT In this study, the sample population was all Employees in the Public Elementary School 005 Kelurahan Air Putih of Samarinda Ulu, the variable researches are a discipline of work is the awareness and the willingness of a person to obey all the rules of institutions and social norms in force as well as aware of the duties and responsibilities and performance of employees is the real behavior displayed by an employee as the resulting performance by employees in accordance with its role within the company. The used of data analysis techniques are 1) The validity test is used to measure whether or not a legitimate or valid questionnaires. 2) Test is a test to measure the reliability of a questionnaire which is an indicator of variables or constructs. 3) The regression analysis is the study of the dependence of the dependent variable (bound) with one or more independent variables (explanatory variables / free). 4) test the hypothesis in which the regression function assessment in estimating the actual value can be measured from the Goodness of Fit, at least this can be measured by the value of t test, and the coefficient of determination. The results showed that the work discipline employees positive and significant effect on the performance of office workers Elementary School 005 Kelurahan Air Putih Kecamatan Samarinda Ulu Samarinda City, based on the distribution of respondents to variable discipline of employees that the percentage of strongly agree contained in second statement  is equal 81% (Employees always take the time to work). At sixth statement that is equal to 81% (employee always pay attention about the tidiness of the uniform and haircut). The conclusions can be seen from the analysis of determination coefficient obtained value of Adjusted R Square (R2) of 0.919 it means that 91.9% of performance variables can be explained by the variable work discipline, while the remaining 8.1% can be explained by other variables that is not examined in this study.